In vivo Measurement of Intraosseous Vascular Haemodynamic Markers in Human Bone Tissue Utilising Near Infrared Spectroscopy - Meertens, Robert; Knapp, Karen M.; Strain, William David; Casanova, Francesco; Ball, Susan; Fulford, Jon; Thorn, Clare (Frontiers in Physiology, 2021)
Objective: Poor vascular health is associated with reduced bone strength and increased risk of fragility fracture. However, direct measurement of intraosseous vascular health is difficult due to the density and mineral content of bone. We investigated the feasibility of using a commercially available continuous wave near infrared spectroscopy (NIRS) system for the investigation of vascular haemodynamics in human bone in vivo. Approach: An arterial occlusion protocol was developed for obtaining haemodynamic measurements of the proximal tibia and lateral calf, including assessment of the protocol’s intra operator reproducibility. For thirty-six participants, intraosseous haemodynamics derived by NIRS were compared to alternative tests of bone health based on dual x-ray absorptiometry (DXA) testing and magnetic resonance imaging (MRI). Main Results: NIRS markers of haemodynamics of the proximal tibia demonstrated acceptable reproducibility, comparable with reproducibility assessments of alternative modalities measuring intraosseous haemodynamics, and the use of NIRS for measuring muscle. Novel associations have been demonstrated between haemodynamic markers of bone measured with NIRS, and body composition and bone mineral density measurements obtained with both DXA and MRI. Significance: NIRS provides inexpensive, non-invasive, safe, and real time data on changes in oxygenated and deoxygenated haemoglobin concentration in bone at the proximal tibia. This study has demonstrated the potential for NIRS to contribute to research investigating the pathophysiological role of vascular dysfunction within bone tissue, but also the limitations and need for further development of NIRS technology.